Brain Metabolisms Involved in Self-Reported Quality of Mobility in Parkinson’s Disease - Fei, Lu; Liu, Feng-Tao; Liu, Yi-Qi; Ge, Jing-Jie; Lu, Jia-Ying; He, Shu-Jin; Sun, Yi-Min; Wu, Jian-Jun; Zuo, Chuan-Tao; Wang, Jian (Frontiers in Neuroscience, 2020)
Background：Objective motor ratings and subjective motor complaints are both widely used in Parkinson’s disease (PD). However, the objective basis to the self-perceived mobility quality is still not well elucidated. Purposes: We aimed to figure out the relevancy between the UPDRS motor scores and PDQ39 mobility sub-scores, and further explore whether physician-assessed motor dysfunctions and patients-reported mobility deficits have some shared mechanisms. Methods: 49 patients with PD who completed the PDQ39 scale were retrospectively included. The relevancy between mobility quality and UPDRS scores was assessed, as well as the related presynaptic dopaminergic binding (11C-CFT) and glucose metabolism (18F-FDG) in this dual-tracer PET imaging study. Results: Modest correlation was found between UPDRS motor score and the PDQ39 mobility sub-score (r=0.440, p=0.002). No correlation was found between PDQ39 mobility SI and the dopaminergic lesions in putamen; however, the strict correlation was found with the UPDRS motor scores. In terms of global PD related pattern (PDRP) scores, the two motor scores both correlated strictly. In the further regional metabolism exploration, cerebellum correlated positively with PDQ39 mobility sub-scores, and the frontal and parietal regions mainly correlated negatively with the motor quality scores. Conclusions: UPDRS motor scores and PDQ39 mobility scores were only modestly correlated. The mechanisms involved under mobility quality were beyond dopaminergic deficiency, including motor related cerebellum hyper-metabolism and non-motor related frontal hypo-metabolism. Conclusively, the self-reported mobility experience may have the neurophysiological basis related to both motor and non-motor manifestations in PD.